(untitled) (Phoenix: International Multidisciplinary Research Journal ( Peer reviewed High Impact Journal ), 2026)
Background of the Study: Intensive care units (ICUs) are dedicated for enhancing the survival of critically ill patients and require constant monitoring due to life threatening conditions. Vital signs is a cardinal indicator of a patient's health status. Modified Early Warning Score (MEWS), a scoring system based on vital signs, helps standardize patient assessment and allows for early recognition of patient’s delicate distinctions, prompting appropriate escalation of care. Aim: To find out the association of physiological parameters with selected socio- demographic variables and selected clinical variables among critically ill patients. Methods: An observational study using a descriptive approach was conducted to assess the physiological parameters among (n=140) critically ill patients. Data was collected using sociodemographic, clinical variables and physiological variables were recorded using MEWS score from cardiac monitor. Participants were selected using convenience sampling method who were admitted in ICUs at tertiary care hospital, Madikeri between January 2025 to February 2025. Data was analyzed and interpreted by applying descriptive and inferential statistical methods Results: In this study, out of 140 respondents 39(27.9%) of patients showed a MEWS scoring of 3-4 indicating the critically ill patients require continuous observation and monitoring in order to prevent further complications. Also 47(33.6%) of patients were showing signs of respiratory failure (MEWS ≥ 5) which indicated higher level of care On the other hand, it is observed that there is a significant association between oxygen saturation (%) with age (χ2=8.192, p=0.042), temperature(0c) with gender (χ2=4.726, p=0.030), systolic blood pressure(mmHg) with monthly family income ((χ2=8.35, p=0.039) at 0.05 level of significance. There is also significant association between respiratory rate(breaths/min) with GCS category (χ2=6.542, p=0.038) and critically ill category (χ2=13.524, p=0.001), systolic blood pressure(mmHg) with patients on regular medication use (χ2=5.040, p=0.025) at 0.05 level of significance. Conclusion: MEWS is a simple, physiological score to prevent delay in intervention or transfer of critically ill patients. It is an important risk management tool that should be implemented for all ICU patients